Exhausted PD-1+ TOX+ CD8+ T Cells Arise Only in Long-Term Experimental Trypanosoma cruzi Infection - Gálvez, Rosa Isela; Jacobs, Thomas (Frontiers in Immunology, 2022)
Infection with Trypanosoma cruzi remains the most important neglected zoonosis in Latin America. This infection does not lead to specific symptoms in the acute phase, but chronic infection can result in Chagas disease (CD) with cardiac and/or gastrointestinal manifestations that can lead to death. CD8+ T cells are highly effective and essential to control this infection, but fail to eliminate all parasites. In this study, we show that the CD8+ T cells are modulated by the transient induction of co-inhibitory receptors during acute infection of C57BL/6 mice. Therapeutic intervention strategies with blocking antibodies only had a marginal effect on the elimination of parasite reservoirs. Only long-term chronic infection gave rise to dysfunctional CD8+ T cells, which were characterized by high expression of the inhibitory receptor PD-1 and the co-expression of the transcription factor TOX, which plays a crucial role in the maintenance of the exhausted phenotype. PD-1+ TOX+ CD8+ T cells isolated from the site of infection produced significantly less IFN-, TNF- and Granzyme B than their PD-1- TOX- CD8+ T cell counterparts after T. cruzi-specific stimulation ex vivo. Taken together, we provide evidence that, in the context of experimental infection of mice, the magnitude of the CD8+ T cell response in the acute phase is sufficient for parasite control and cannot be further increased by targeting co-inhibitory receptors. In contrast, persistent long-term chronic infection leads to an increase of exhausted T cells within the tissues of persistence. To our knowledge, this is the first description of infection-induced CD8+ T cells with an exhausted phenotype and reduced cytokine production in muscles of T. cruzi-infected mice.